Impact of Occupational Stress and Fatigue on Menstrual Cycle Characteristics among Female Biddokkes Workers - Ike Prafitasari; Anndy Prastya; Michael Chevin Al Afgani (Al-Hijrah Indonesia, 2026)
Background: Menstrual cycle irregularity is a reproductive health problem that may be influenced by occupational stress and work fatigue. Objective: This study examined the relationship between stress level and work fatigue with menstrual cycle regularity among female formal workers at Biddokkes Polda Jawa Timur. Methods: An analytical observational study with a cross-sectional design was conducted among 88 female former workers selected from a population of 100 workers. Stress, work fatigue, and menstrual cycle data were collected using structured questionnaires, including the Unimma Work Fatigue Instrument for fatigue assessment and PSS-10 for occupational stress. Data were analyzed using Spearman correlation. Results: Most respondents reported very severe stress (39.8%), severe work fatigue (44.3%), and irregular menstrual cycles (65.9%). Spearman's correlation analysis revealed strong, significant negative correlations between stress level (p < 0.001; r = -0.850) and work fatigue (p < 0.001; r = -0.870) and the menstrual cycle. Conclusion: Higher stress levels and work fatigue were significantly associated with menstrual cycle irregularity among female formal workers. Workplace stress management, fatigue control, and reproductive health monitoring are needed to protect female workers' health.